Investigation of the physicochemical, antioxidant, rheological, and sensory properties of ricotta cheese enriched with free and nano‐encapsulated broccoli sprout extract. Issue 11 (3rd August 2022) - Azarashkan, Zahra; Motamedzadegan, Ali; Ghorbani‐HasanSaraei, Azade; Biparva, Pourya; Rahaiee, Somayeh
Abstract: This study aimed to produce the functional ricotta cheese using broccoli sprouts extract (BSE) and to evaluate its physicochemical, antioxidant, rheological, and sensory properties. The BSE nano‐liposome was nano‐encapsulated into basil seed gum (BSG) and was incorporated into the ricotta cheese formulation in two forms of free and nano‐capsules in two levels of 3% and 5% w/w. The measurements were conducted during a 15‐day storage period at 4–6°C. The results showed that the titratable acidity, hardness, and chewiness of cheeses were increased and the pH, moisture, total phenol content (TPC), and antioxidant activity were decreased ( p  < .05). With the addition of BSE concentration, the TPC and antioxidant activity increased significantly ( p  < .05) and applying the nano‐encapsulation method for BSE led to better preservation of bioactive compounds. Based on the rheological results, viscoelastic solid behavior and a weak gel were observed in all cheese samples. The results of sensory evaluation demonstrated that cheeses containing free extract had lower flavor and overall acceptability scores than other samples, which indicates that the nano‐encapsulation covered the undesirable flavor of the BSE. Generally, during the 15‐day cold storage period, the highest sensory acceptance and functional activity were related to the samples containing nano‐encapsulated BSE, especially at the 5% level. Abstract : We were produced the functional Ricotta cheese using encapsulated broccoli sprouts extract (BSE) (3% and 5% w/w) nanoliposomes into basil seed gum successfully. Physicochemical, antioxidant, rheological, and sensory properties indicated that during a 15‐day storage period at 4‐6 C, the level of BSE 5% was the best. Viscoelastic solid behavior and a weak gel were observed in all cheese samples and the sensory evaluation indicated the nano‐encapsulation covered the undesirable flavor.